Addressing metabolite safety during first-in-man studies using 14C-labeled drug and accelerator mass spectrometry. (July 2010) - Lappin, Graham; Seymour, Mark
Active drug metabolites formed in humans but present in relatively low abundance in preclinical species can lead to unpredicted adverse effects during clinical use. The regulatory guidelines in recent years have therefore required that the metabolism of a drug be quantitatively compared between preclinical species and human at the earliest practicable stage of drug development. Amongst the variety of methods available, inclusion of low radioactive doses of 14 C drug in first-in-man studies coupled to the sensitive analytical technology of accelerator MS (AMS) has found utility. Measurement of 14 C by AMS allows for quantification of metabolites, even if their structures are unknown, and, when used in conjunction with LC–MS, can provide both quantitative and structural data. This review examines a typical approach to using AMS and associated analytical methods in addressing the regulatory guidelines and discusses a number of possible scenarios including the question of steady state.